Biomedical inorganic polymers : bioactivity and applications of natural and synthetic polymeric inorganic molecules - Wang, Xiaohong; Schröder, Heinz C. (Progress in Molecular and Subcellular Biology,, 2013)
This book summarizes the present state of knowledge on a number of inorganic polymers with respect to their potential biomedical applications. In recent years, inorganic polymers have attracted much attention in nano-biomedicine, in particular in the areas of regenerative medicine and drug delivery. The growing interest in these polymers has been further accelerated by the development of new synthetic and analytical methods in the field of nanotechnology and nanochemistry. Examples of biomedical inorganic polymers that have been proven to exhibit biomedical effects and/or have been applied in preclinical or clinical trials are polysilicate / silica glass (such as naturally formed "biosilica" and synthetic "bioglass") and inorganic polyphosphate. Some biomedical inorganic polymers have already been applied e.g. as "bioglass" for bone repair and bone tissue engineering, or are used in food processing and in dental care (inorganic polyphosphates). However, there are a number of further biological and medicinal properties of these polymers that have been elucidated in the last few years but not yet been applied for treatment of humans. In addition to polysilicates and polyphosphate, there are a series of other inorganic polymers including polyarsenate and polyvanadate, the biological / biomedical properties of which have been only marginally studied so far. Moreover, the combined application of inorganic polymers and organic polymeric molecules (formation of organic-inorganic hybrid materials) provides a variety of new materials with novel property combinations and diverse applications in nanomedicine.